The role of manganese dysregulation in neurological disease: emerging evidence. Issue 11 (November 2021) - Budinger, Dimitri; Barral, Serena; Soo, Audrey K S; Kurian, Manju A
Summary: Manganese is an essential trace metal. The dysregulation of manganese seen in a broad spectrum of neurological disorders reflects its importance in brain development and key neurophysiological processes. Historically, the observation of acquired manganism in miners and people who misuse drugs provided early evidence of brain toxicity related to manganese exposure. The identification of inherited manganese transportopathies, which cause neurodevelopmental and neurodegenerative syndromes, further corroborates the neurotoxic potential of this element. Moreover, manganese dyshomoeostasis is also implicated in Parkinson's disease and other neurodegenerative conditions, such as Alzheimer's disease and Huntington's disease. Ongoing and future research will facilitate the development of better targeted therapeutical strategies than are currently available for manganese-associated neurological disorders.